Seasonal and Tidal Dynamics of Water Temperature, Salinity, Chlorophyll-a, Suspended Particulate Matter, Particulate Organic Matter, and Zooplankton Abundance in a Shallow, Mixed Estuary (Bahía Blanca, Argentina) - Menendez, Maria Clara (2015)
Estuaries are characterized by a variety of interrelated, abiotic and biotic, structural components and intensive physical, chemical, and biological processes. The aim of this study was to investigate the seasonal- and tidal-mediated variability in water temperature, salinity, suspended particulate matter (SPM), particulate organic matter (POM), chlorophyll-a (Chl-a), and zooplankton abundance in the Bahía Blanca estuary, Argentina. The underlying mechanisms responsible for the observed variability are also discussed. Sampling was carried out every two months (December 2004–April 2006) during 14-h tidal cycles in a fixed station located in the inner zone of the estuary. Vertical profiles of temperature and salinity and water samples were obtained at the surface and the bottom to determine SPM, POM, Chl-a, and zooplankton. SPM (97.3 ± 6.9 mg L−1) showed a strong seasonality, mainly attributed to biological activity. POM concentration (1539 ± 107.6 mgC m−1) was high, possibly derived from vascular plants and benthic microalgae. Chl-a (6.91 ± 0.73 mg m−3) and zooplankton (2024.23 ± 9.16 individuals m−3) also showed a seasonal pattern, with higher concentrations in the summer. During the tidal cycle, the highest amounts of the measured variables were observed during the ebb tide. The results highlight the strong variability in the physicochemical and biological variables at different time scales in mesotidal, temperate estuaries. It is essential to take into account this variability in any monitoring program performed in a temperate system dominated by such a tidal regime.